Optimization of arachidonic acid production from Mortierella alpina PRAO7-10 by response surface methodology - Malaiwong, Narissara; Yongmanitchai, Wichien; Chonudomkul, Duenrut (Agriculture and Natural Resources, 2016)
Arachidonic acid (ARA) is an essential fatty acid in animal nutrition. The filamentous fungus Mortierella alpina has been widely used for production of ARA. The strain M. alpina PRAO7-10 was isolated from a soil sample in northern Thailand. Seven parametersdtemperature, pH, percentage of medium volume per flask volume (% v/v) and glucose, KNO3, K2HPO4 and soy isolate concentrationsdaffected the biomass and ARA production of this fungus and were determined using the Plackett-Burman statistical design technique. The results revealed that temperature and % v/v played a significant role in the biomass and ARA production while glucose and soy isolate only affected the ARA production. Therefore, they were chosen for optimization using a central composite design and response surface methodology to maximize the dried cell weight (DCW) and ARA production. The optimal values for the temperature, % v/v, glucose concentration and soy isolate concentration were 25.06 oC, 14.16%, 6.67% and 0.48%, respectively. Under these optimal culture conditions, the maximum DCW and ARA production were 52.64 g/L and 6.76 g/L, respectively. Validation of the optimal conditions showed that deviations in DCW and ARA of the experimental data from the predicted values were 1.72% and 2.42%, respectively, suggesting the suitability of the model employed and that the experimental designs were effective for the optimization of the DCW and ARA production.